Application Of Music Therapy Techniques in The Educational Sector University Students Virtual Modality (Docentes 2.0 Journal, 2022)
Scientific music therapy is a modern therapeutic technique that has generated a progressive interest among the scientific community. It is used in the health sector for patients subjected to minor invasive interventions to relieve their pain, prevent, restore, increase their physical and mental health. For this reason, the objective was to propose the adaptation based on the five music therapy techniques used in health, to be developed in university education. The research was developed under the theoretical method, positivist paradigm, descriptive-type quantitative approach, and non-experimental design. A questionnaire was used to discover and describe which techniques had been most beneficial to the students. The main findings expressed by the 93 subjects investigated, 49.5% found strategies to improve: mental health, emotional well-being, and creative expression more useful.On the other hand, 32.3% found it more critical to make group musical improvisations of a Trujillo marinera sung, danced, accompanied by family. For future research, as a reflection of the researchers, we consider working on a program that lasts 16 weeks to measure other dimensions of participants' emotions. It was concluded that adapting music therapy techniques is helpful in the educational sector; above all, those that lead to improving mental health; however, they need to be applied concerning the contents of group interaction between family members and colleagues in the virtual classroom.
Keywords: Techniques; music therapy; therapy